Smart Wearable Technologies as Resources for Consumer Agency in Well-Being. Issue 2 (May 2023) - Tikkanen, Hannu; Heinonen, Kristina; Ravald, Annika
Consumers are increasingly expected to be active in managing their personal well-being. Agency, meaning individuals' ability to reflect on their circumstances, effect change, and act independently, constitutes an important means for consumer well-being. To a growing extent, consumers are using smart technologies, such as wearable devices and applications, to better manage their well-being. However, how interactions with wearables improve and affect consumer agency for well-being is underexamined. The aim of this study is to explore how consumers use smart wearable technologies as resources for agency in managing their well-being. Drawing on psychological and sociological literature on agency as well as qualitative data from users of various wearable devices, the authors distinguish individual and contextual levels of agency, in which knowing and acting constitute two types of smart wearable technology use. From these dimensions, they conceptualize a framework with four types of technology use for well-being: (1) self-improvement, (2) justification, (3) adaptation, and (4) activism. The authors discuss the theoretical and managerial implications of this framework with the aim of improving consumer agency for well-being through smart technology.